Eigenstrain reconstruction method in linear friction welded aluminium alloy and MMC plates - Jun, T; Korsunsky, A (2010)
In the present paper, we put forward a combined experimental and modelling approach based on the inverse eigenstrain methodology. The approach allows approximate reconstruction of the complete strain/stress state in the entire component. The resulting description is qualitatively different from the raw input data, since it is continuous, complete and consistent (the latter in terms of satisfying equilibrium, compatibility and boundary conditions). This is a significant improvement compared with the experimentally obtained limited knowledge of stress components at a selected number of measurement points, or from simple interpolation between these points. In the current study, the methodology is applied to the interpretation of diffraction strain measurements obtained by neutron and synchrotron X-ray scattering in linear friction welds between aluminium-based materials. We introduce a novel approach and present the mathematical framework that allows the eigenstrain reconstruction method (ERM) to be extended so as to provide a rational resolution of the important issue of unstrained lattice parameter (d 0) determination. Different implementations of the general inverse eigenstrain principle are considered and compared. Copyright © 2010 John Wiley and Sons, Ltd. Copyright © 2010 John Wiley and Sons, Ltd.